Genetic associations with neuroendocrine tumor risk: results from a genome-wide association study. Issue 8 (August 2016) - Du, Yeting; Ter-Minassian, Monica; Brais, Lauren; Brooks, Nichole; Waldron, Amanda; Chan, Jennifer A; Lin, Xihong; Kraft, Peter; Christiani, David C; Kulke, Matthew H
Abstract : The etiology of neuroendocrine tumors remains poorly defined. Although neuroendocrine tumors are in some cases associated with inherited genetic syndromes, such syndromes are rare. The majority of neuroendocrine tumors are thought to be sporadic. We performed a genome-wide association study (GWAS) to identify potential genetic risk factors for sporadic neuroendocrine tumors. Using germline DNA from blood specimens, we genotyped 909, 622 SNPs using the Affymetrix 6.0 GeneChip, in a cohort comprising 832 neuroendocrine tumor cases from Dana-Farber Cancer Institute and Massachusetts General Hospital and 4542 controls from the Harvard School of Public Health. An additional 241 controls from Dana-Farber Cancer Institute were used for quality control. We assessed risk associations in the overall cohort, and in neuroendocrine tumor subgroups. We identified no potential risk associations in the cohort overall. In the small intestine neuroendocrine tumor subgroup, comprising 293 cases, we identified risk associations with three SNPs on chromosome 12, all in strong LD. The three SNPs are located upstream of ELK3, a transcription factor implicated in angiogenesis. We did not identify clear risk associations in the bronchial or pancreatic neuroendocrine subgroups. This large-scale study provides initial evidence that presumed sporadic small intestine neuroendocrine tumors may have a genetic etiology. Our results provide a basis for further exploring the role of genes implicated in this analysis, and for replication studies to confirm the observed associations. Additional studies to evaluate potential genetic risk factors for sporadic pancreatic and bronchial neuroendocrine tumors are warranted.